Fabrication of dense SiSiC ceramics by a hybrid additive manufacturing process. Issue 2 (5th October 2021) - Pelanconi, Marco; Bianchi, Giovanni; Colombo, Paolo; Ortona, Alberto
Abstract: In this work, we report the fabrication of Silicon infiltrated Silicon Carbide (SiSiC) components by a hybrid additive manufacturing process. Selective laser sintering of polyamide powders was used to 3D print a polymeric preform with controlled relative density, which allows manufacturing geometrically complex parts with small features. Preceramic polymer infiltration with a silicon carbide precursor followed by pyrolysis (PIP) was used to convert the preform into an amorphous SiC ceramic, and five PIP cycles were performed to increase the relative density of the part. The final densification was achieved via liquid silicon infiltration (LSI) at 1500°C, obtaining a SiSiC ceramic component without change of size and shape distortion. The crystallization of the previously generated SiC phase, with associated volume change, allowed to fully infiltrate the part leading to an almost fully dense material consisting of β‐SiC and Si in the volume fraction of 45% and 55% respectively. The advantage of this approach is the possibility of manufacturing SiSiC ceramics directly from the preceramic precursor, without the need of adding ceramic powder to the infiltrating solution. This can be seen as an alternative AM approach to Binder jetting and direct ink writing for the production of templates to be further processed by silicon infiltration. Abstract :